The Evolution of English in Nepalese Education: Policies and Practices - Sapkota, Narayan Prasad (English Language Teaching Perspectives, 2025)
This research explores the historical development of the English language and English Medium Instruction (EMI) in Nepal, examining its evolution, policy shifts, and sociocultural implications. Drawing on an extensive library study, the research traces the trajectory of English education from its initial introduction in the 17th century through trade and missionary activities to its current prominence in Nepal’s education system. Key milestones include the establishment of Durbar School in 1853, policy reforms following the Rana regime’s fall in 1951, and contemporary efforts to balance multilingual education with the demand for English proficiency. Findings reveal that English has transitioned from being an elite language to a widely taught subject, with EMI gaining popularity in private schools and gradually being adopted in public schools. However, significant challenges persist, including disparities between private and public schools, inadequate teacher training, and the marginalization of indigenous languages. Policies have oscillated between promoting mother tongue-based instruction and integrating English, reflecting tensions between globalization and cultural preservation. This study underscores the need for equitable and context-sensitive policies to address these challenges. It advocates for strengthening teacher capacity, developing multilingual teaching resources, and fostering awareness about the value of Nepal’s linguistic diversity. By adopting a balanced approach, Nepal can leverage the opportunities presented by English education while preserving its rich cultural and linguistic heritage.